Prognostic implications of mitral regurgitation in patients after cardiac resynchronization therapy. (13th July 2016) - Cipriani, Manlio; Lunati, Maurizio; Landolina, Maurizio; Proclemer, Alessandro; Boriani, Giuseppe; Ricci, Renato P.; Rordorf, Roberto; Matassini, Maria Vittoria; Padeletti, Luigi; Iacopino, Saverio; Molon, Giulio; Perego, Giovanni B.; et al.
Abstract: Aim: Mitral regurgitation (MR) is a common finding in patients with heart failure with debatable effects on prognosis. Reduction in MR is one of the mechanisms by which cardiac resynchronization therapy (CRT) exerts its beneficial effects. We investigated the prognostic impact of baseline MR and MR persistence after CRT on outcomes of treated patients. Methods and results: We prospectively followed 1122 CRT patients (66.4 ± 10.3 years, 78% male) who were stratified according to baseline MR severity as having MR− (degree 0–1; n  = 508, 45%) or MR+ (degrees 2–3–4; n  = 614, 55%). In 916 patients (82%) with MR severity data available at 1‐year follow‐up, the annual mortality rate was 3.4 and 6.0 per patient‐year in the MR− and MR+ group, respectively, with a 1‐year incidence rate ratio (IRR) of 1.76 ( P  < 0.001). Similar results were observed for cardiovascular mortality (1‐year IRR 1.72, P  = 0.002). When considering survival according to MR severity after CRT, all‐cause and cardiovascular mortality were lower in the improved than in the worsened group (1‐year IRR 1.87 and 2.33, respectively; both P  < 0.001). Regression analysis showed that absence of MR improvement at follow‐up was a significant independent predictor of both all‐cause and cardiovascular mortality. Conclusions: Baseline significant MR and absence of MR improvement after CRT are strongly predictive of less favourable long‐term survival.